Geographical Labor Market Imbalances by Chiara Mussida and Francesco Pastore - PASNICU, Daniela (Annals of Spiru Haret University. Economic Series, 2016)
The book, entitled Geographical Labor Market Imbalances represents a collective volume of outstanding scientific papers concerning regional issues, which were presented at the XXVII National Conference of Labour Economics organized by AIEL (Italian Association of Labor Economics), the Department of Law of SecundaUniversità di Napoli and the Departments of Economic and Social Sciences of the UniversitàCattolica del SacroCuore (Piacenza), 27-28 September 2012.